2021
DOI: 10.1111/joor.13230
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of low‐level laser therapy with different wavelengths and transcutaneous electric nerve stimulation in the treatment of pain caused by temporomandibular disorders: A systematic review and network meta‐analysis

Abstract: Objective: To assess the efficacy of low-level laser therapy (LLLT) with different wavelengths and transcutaneous electric nerve stimulation (TENS) and explore the optimal wavelength range of laser application in the treatment of pain caused by temporomandibular disorders (TMD).Methods: An electronic search on PubMed, Cochrane Library, Embase, Scopus and Web of Science was undertaken to identify the randomised clinical trials (RCTs) published from database inception to 16 April 2021, aiming to compare the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…One special feature of LLLT is that it does not make contact with skin and can be used even with wounds. In a systematic review and network meta-analysis conducted in 2022, Ren et al explored the optimal wavelength range of laser application, affirming that laser therapy with a wavelength of 910–1100 nm was the most effective [ 87 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One special feature of LLLT is that it does not make contact with skin and can be used even with wounds. In a systematic review and network meta-analysis conducted in 2022, Ren et al explored the optimal wavelength range of laser application, affirming that laser therapy with a wavelength of 910–1100 nm was the most effective [ 87 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…While TENS, LLLT and therapeutic US are useful in pain reduction, systematic reviews and meta-analyses carried out in 2022 have shown that LLLT was the most effective in reducing pain among the three treatment modalities [ 87 , 89 , 90 ]; LLLT was found to be superior to TENS and was also proven to be better in reducing pain than therapeutic US [ 89 ]. Better results could be achieved with higher wavelengths, and wavelengths ranging from 910 nm to 1100 nm were recommended to treat TMD using LLLT [ 87 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Open access exercise (such as masticatory muscle opening, range of motion training and manual TMJ disc manipulation), drug (including analgesics, central muscle relaxants, anxiolytics) and appliance (stabilisation appliance, anterior positioning appliance therapy) therapies. [6][7][8][9][10][11] Conservative treatment, including counselling, exercises, occlusal splint therapy, massage and manual therapies, should be considered the first choice for TMD pain because of their low risk of side effects. Pharmacotherapy and minimally invasive procedures should be considered in the case of severe acute or chronic pain resulting from serious disorders, inflammation and degeneration.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The main TMD therapeutic goals are pain relief, jaw function recovery and quality of life (QOL) improvement 5. Reversible conservative treatments in the initial TMD treatment include physical (such as masticatory muscle massage, hot compress and electrical stimulation therapy), exercise (such as masticatory muscle opening, range of motion training and manual TMJ disc manipulation), drug (including analgesics, central muscle relaxants, anxiolytics) and appliance (stabilisation appliance, anterior positioning appliance therapy) therapies 6–11. Conservative treatment, including counselling, exercises, occlusal splint therapy, massage and manual therapies, should be considered the first choice for TMD pain because of their low risk of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of TMD is considered multifactorial. Biomechanical, neuromuscular, biopsychosocial and neurobiological factors also affected the development of TMD (3). Studies have shown that TMD is more common in women aged 20-40 years (4,5).…”
mentioning
confidence: 99%